1985
DOI: 10.1148/radiology.154.3.2982174
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma with skeletal metastasis.

Abstract: Three patients with symptoms related to metastases from hepatocellular carcinoma are described. The diagnosis of the primary tumor was made at autopsy in two cases and by biopsy in one. The skeletal lesions had a lytic, expansile, and hypervascular appearance. This hypervascularity may lead to bleeding either spontaneously or following biopsy. Hepatocellular carcinoma should be included in the differential diagnosis of osteolytic, expansile, hypervascular metastases, especially when such lesions are encountere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Bone metastases from HCC present as osteolytic, expansile, and hypervascular bone lesions [4,7,8]. Although bone metastasis from HCC is not very frequent, it can be the initial manifestation of HCC in some cases [2,4,9].…”
Section: Discussionmentioning
confidence: 99%
“…Bone metastases from HCC present as osteolytic, expansile, and hypervascular bone lesions [4,7,8]. Although bone metastasis from HCC is not very frequent, it can be the initial manifestation of HCC in some cases [2,4,9].…”
Section: Discussionmentioning
confidence: 99%
“…Such bone metastases have also been observed in patients with renal cell carcinoma and thyroid carcinoma. 22,23 In this study, the most observed anatomical metastatic regions were spine, followed by thorax and pelvis while the most observed sites with FN results on BS were the lower extremity, spine, and pelvis. These findings were compatible with those from previous reports.…”
Section: Discussionmentioning
confidence: 56%
“…It has been reported that bone metastases from HCC are often osteolytic and without obvious new bone formation. 3,22,23 This usually results in low Tc-99m MDP uptake and low sensitivity of BS. Such bone metastases have also been observed in patients with renal cell carcinoma and thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies with a limited number of patients have described the characteristics of bone metastasis from HCC, such as soft tissue formation (15)(16)(17)(18)(19). Kim (14) confirmed the characteristic finding of soft tissue formation at a bone metastasis from a primary hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 81%